Analysis of the Role of the Drug Swallowing Supervisor in Improving Treatment Adherence Drug-Sensitive Tuberculosis Patients in Palembang City - Amedia, Azra; Rahmawaty, Annisa (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2024)
The role of drug swallowing supervisors was needed from the beginning of treatment so that patients could be monitored regularly to prevent drug resistance. This study aimed to determine the role of drug swallowing supervisors in improving treatment adherence of drug-sensitive tuberculosis patients in Palembang City. This research used a qualitative design with a descriptive approach. Eleven informants were determined through purposive sampling technique. Data analysis employed Miles and Huberman's qualitative data analysis model, consisting of data reduction, data presentation, and conclusion. In improving treatment adherence of patients with drug-sensitive tuberculosis in Palembang City, drug swallowing supervisors provided education, motivated, supervised, and accompanied patients during the treatment process until they were declared cured. The role of drug swallowing supervisors greatly influenced patient compliance in undergoing treatment.